The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.1590/1983-21252021v34n206rc
|View full text |Cite
|
Sign up to set email alerts
|

Relative Competitiveness Between Maize Hybrids and Wild Poinsettia

Abstract: Maize is one of the main cereals cultivated worldwide and wild poinsettia is among the weeds that cause damage in grain production. The objective of this study was to evaluate the relative competitive ability of maize hybrids in the presence of a wild poinsettia biotype through experiments in replacement series. In preliminary experiments, it was determined the plant population in which the dry mass becomes constant. For the maize hybrids ‘Agroeste’, ‘Morgan’, ‘Nidera’, and ‘Velox’, as well as the wild poinset… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 20 publications
(67 reference statements)
0
2
0
Order By: Relevance
“…In crops, in general, the density of cultivated plants is usually constant, while the density of weeds varies according to the soil seed bank, and environmental and management conditions that change the level of infestation and competitiveness of species (AGOSTINETTO et al, 2013;WANDSCHEER et al, 2014;FRANDOLOSO et al, 2019;BRANDLER et al, 2021). Thus, in competition studies involving crops and weeds, there is a need to evaluate the density of plants in the competitive process, the influence of variation in the proportion between species living in community, and also the effect that different populations associated or not can cause in morphological plant traits (WANDSCHEER et al, 2014;FRANDOLOSO et al, 2019;GALON et al, 2021a).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In crops, in general, the density of cultivated plants is usually constant, while the density of weeds varies according to the soil seed bank, and environmental and management conditions that change the level of infestation and competitiveness of species (AGOSTINETTO et al, 2013;WANDSCHEER et al, 2014;FRANDOLOSO et al, 2019;BRANDLER et al, 2021). Thus, in competition studies involving crops and weeds, there is a need to evaluate the density of plants in the competitive process, the influence of variation in the proportion between species living in community, and also the effect that different populations associated or not can cause in morphological plant traits (WANDSCHEER et al, 2014;FRANDOLOSO et al, 2019;GALON et al, 2021a).…”
Section: Introductionmentioning
confidence: 99%
“…This result indicates that the crop shows less damage than the weed from competition, since the weed presented values very far from those expected, that is, the competitor presented a concave line with damage to the growth in EP, DC, AF, and MS in practically all the proportions of plants tested (Figures2, 3, 4, and 5). Likewise,Wandscheer and Rizzardi (2013), when studying the competition between maize and Chloris distichophylla observed that the hypothetical values established for the crop did not change when there was competition with the weed; the crop maintained its relative productivity equivalent to monoculture conditions Galon et al (2021a). when evaluating the relative competitiveness of Euphorbia heterophylla when infesting different maize hybrids, denoted that the competitor also presented values below the hypothetical line (concave lines), indicating that the competition was harmful to the weed.…”
mentioning
confidence: 99%